The Analysis of the Palu Bay Ecosystem Health Index, Central Sulawesi, using McKinnon's Framework for Environmental Health - Achmad Rizal (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
Human activities are believed to have caused significant damage to ecosystems. In fact, a healthy ecosystem must always be maintained so that it can continue to provide its services to humanity. The research aims to assess the health of the coastal ecosystem in Palu Bay, Central Sulawesi. Ecosystem health is measured by establishing an ecosystem health index (EHI) using McKinnon's framework for environmental health. The indicators set to measure the EHI are, first, the habitat (coastal water connectivity, mangrove forest stand condition, and pollution/clarity). Second, the biological resources/species (catch diversity and catch quantity). Third, the socio-economic conditions (fishermen's income and willingness to participate in coastal ecosystem management). Overall, the obtained EHI value is 0.47. The index falls into the moderate category. However, three indicators fall into the poor category, i.e., pollution, mangrove forests, and fishermen's income. To improve this health index, long-term efforts are needed, including, first, maintaining the integrity of the coast by reducing physical development; second, raising environmental awareness about cleanliness; third, implementing rules for the use of fishing gear and environmentally friendly fishing methods; and fourth, strengthening environmental awareness among the society.